Regulation of p27(Kip1) and p57(Kip2) Functions by Natural Polyphenols - Russo, Gian Luigi (Biomolecules, 2020)
In numerous instances, the fate of a single cell not only represents its peculiar outcome but also contributes to the overall status of an organism. In turn, the cell division cycle and its control strongly influence cell destiny, playing a critical role in targeting it towards a specific phenotype. Several factors participate in the control of growth, and among them, p27(Kip1) and p57(Kip2), two proteins modulating various transitions of the cell cycle, appear to play key functions. In this review, the major features of p27 and p57 will be described, focusing, in particular, on their recently identified roles not directly correlated with cell cycle modulation. Then, their possible roles as molecular effectors of polyphenols’ activities will be discussed. Polyphenols represent a large family of natural bioactive molecules that have been demonstrated to exhibit promising protective activities against several human diseases. Their use has also been proposed in association with classical therapies for improving their clinical effects and for diminishing their negative side activities. The importance of p27(Kip1) and p57(Kip2) in polyphenols’ cellular effects will be discussed with the aim of identifying novel therapeutic strategies for the treatment of important human diseases, such as cancers, characterized by an altered control of growth.